Illuminating Women in the World of St. Jerome. When Policy and Practice Diverged - Faber, Rebecca (Forum Theologicum Sardicense, 2025)
Women’s presence was ubiquitous in the life of Jerome of Stridon c. 347-420 as in that of many early church fathers. This paper looks at the Christian stance on women, sex and marriage from the optic of the “life of angels” interpreted by Jerome in the Celibacy debates of 382–393. It includes profiles of aristocratic women in Rome who influenced him and who despite cultural limitations became leaders with reference to Jerome’s legacy that endured beyond the late fourth century discord. A major intellectual force, Jerome rose to prestige and honors, but fell to disgrace. Celi-bate women stood loyally by his side and rescued him